2012
DOI: 10.4161/auto.20159
|View full text |Cite
|
Sign up to set email alerts
|

Compromised autophagy byMIR30Bbenefits the intracellular survival ofHelicobacter pylori

Abstract: Helicobacter pylori evade immune responses and achieve persistent colonization in the stomach. However, the mechanism by which H. pylori infections persist is not clear. In this study, we showed that MIR30B is upregulated during H. pylori infection of an AGS cell line and human gastric tissues. Upregulation of MIR30B benefited bacterial replication by compromising the process of autophagy during the H. pylori infection. As a potential mechanistic explanation for this observation, we demonstrate that MIR30B dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 41 publications
6
114
0
Order By: Relevance
“…More specifically, s1 VacA binds to the low-density lipoprotein receptor-related protein-1 triggering reactive oxygen speciesinduced autophagy (68). Compromised autophagy has been associated with increased capacity of H. pylori to survive in the intracellular environment (69). Interestingly, while both strains induced systemic Th1 responses and caused an expansion in the cytotoxic cell compartments, we found differences in their ability to persist in the stomach mucosa.…”
Section: Differentiation Of Naive Cd4mentioning
confidence: 37%
“…More specifically, s1 VacA binds to the low-density lipoprotein receptor-related protein-1 triggering reactive oxygen speciesinduced autophagy (68). Compromised autophagy has been associated with increased capacity of H. pylori to survive in the intracellular environment (69). Interestingly, while both strains induced systemic Th1 responses and caused an expansion in the cytotoxic cell compartments, we found differences in their ability to persist in the stomach mucosa.…”
Section: Differentiation Of Naive Cd4mentioning
confidence: 37%
“…Then, the cells were trypsinized and analyzed using a FACScan flow cytometer and CellQuest software, as previously published. 39 Statistical analyses were performed as described above. Monodansylcadaverine staining MDC staining was used to quantify the induction of autophagy in Caco-2 cells.…”
Section: Acridine Orange Stainingmentioning
confidence: 99%
“…[23][24] Importantly, several bacteria can make use of miRNAs to participate in modulating autophagy by directly targeting autophagy-related genes, such as BECN1, ATG12, RHEB, ATG5, and ATG16L1. [14][15][16]25 Therefore, involvement of miRNAs in regulating autophagy is undoubtedly worth further investigation. In our model, B. pseudomallei infection increased 3 novel miRNAs, MIR4458, MIR4667-5p and MIR4668-5p, by different time course and spatial expression patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has indicated that dysregulated miRNAs expression is associated with the evasion of autophagy, with several intracellular bacteria. [14][15][16][17] Thus, understanding the molecular mechanisms of autophagy modulation in host response to B. pseudomallei infection is crucial to current and future therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%